Unwanted and unwelcome: sexual harassment in the Malaysian workplace - Ng, Cecilia; Othman, Jamilah (Taylor & Francis, 2002)
While sexual harassment in the workplace has been recognized as a serious misconduct in the West since the 1980s, it has only been recently acknowledged in the Asian region. Research in the Malaysian workplace revealed that 38 percent of women respondents had experienced one or more forms of harassment, with younger women in lower occu pational categories forming a significant proportion of the victims. It was also interesting to note that 32 percent of male respondents stated that they had experienced sexual harassment. Despite the existence of sexual harassment policies in the six pioneer companies studied, differential perceptions regarding the issue persist. Sexual harassment as issue and as process is highly contested with men noticing and rating less harassment than women. While women are forced to accommodate such behavior as part of the work culture, they are also resisting in various ways, including lodging formal reports. Sexual harassment reflects the unequal power relations between women and men in society with sexuality being used as a part of this control. Indeed, buttressed by religious ideology, the prob lematic of sexual harassment is utilized as a tool to control female sexuality, dressing, and behavior, especially of Muslim women. © 2002, Sage Publications. All rights reserved.